HITO: Pseudocode compiler with graphics library - Mamani Vilca, Ecler (2019)
HITO is a compiler designed for teaching programming logic. It consists on 3 modules. The first one compiles algorithms in pseudo code. The language was defined using BNF notation without checking possible errors by syntactic and semantic analyzers. The second one allows you to translate the pseudo code to C++ programming languages, Java and C#. The third one allows you to draw primitive’s graphics. The software was developed with XP methodology. System and usability unitary test were performed. The results of the evaluation regarding the syntax of the algorithms were "Strongly agree" and "agree" valuation given for 9 experts. It was a descriptive level research with application type.